A systematic approach to medical decision-making of uncommon clinical pictures a case of ulcerative skin lesions by palm tree thorn injury and a one-year follow-up. - Corrao, Salvatore
In clinical practice, the clinician is challenged with symptoms and/or signs at times apparently insoluble by diagnostic and/or therapeutic means. We propose that in these cases, we have to use an EBM approach in which evidence may be looked up in every available clinical report and bibliographic databases are used for searching that evidence. We report on a case of ulcerative skin lesions apparently insoluble by expert dermatologists following a conventional diagnostic and therapeutic process. We use this case report for illustrating a systematic approach to resolve diagnostic and therapeutic questions using a bibliographic database search (like MEDLINE and EMBASE). Both a systematic approach to bibliographic databases and a critically appraised topic on a case reports (or case series) are needed to 'rehabilitate' low-level evidences (that is a case report or case series) to a higher level when we approach decision-making of uncommon clinical pastures. We demonstrate the possibility of using bibliographic databases to search and retrieve useful information for decision-making of uncommon clinical pictures. The method we have proposed can be applied in every area of the world, especially in rural areas. Finally, an Internet-shared database of uncommon clinical pictures with critically appraised topics could be useful in saving more time.
Keywords: Medical decision-making.; Uncommon clinical pictures; Ulcerative skin lesions; Palm tree; Thorn injury